2011
DOI: 10.1177/1948550611425194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence That Positive Moods Cause Sociability

Abstract: Although intuitive and predicted by the broaden-and-build theory of positive emotions, previous research has not seriously tested the idea that positive moods can cause sociability. The authors developed a new measure to assess preferences for social (vs. nonsocial) situations, carefully controlling for the fact that social situations are, on average, also more pleasant. Across two additional experiments (combined n ¼ 237), the authors induced positive, negative, and neutral moods with film clips (betweensubje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…First, positive emotions and anxiety were not experimentally manipulated. Although a temporal statistical relationship was found between increases in pleasantness and connectedness over time, experimental manipulations intended to induce differential affective states would offer stronger evidence to support positive emotions as a causal process underlying the formation of new social connections (e.g., Whelan & Zelenski, 2012). Second, all participants met diagnostic criteria for SAD and displayed elevated symptoms of social anxiety.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…First, positive emotions and anxiety were not experimentally manipulated. Although a temporal statistical relationship was found between increases in pleasantness and connectedness over time, experimental manipulations intended to induce differential affective states would offer stronger evidence to support positive emotions as a causal process underlying the formation of new social connections (e.g., Whelan & Zelenski, 2012). Second, all participants met diagnostic criteria for SAD and displayed elevated symptoms of social anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Neural systems that regulate responses to the anticipation and receipt of social reward cues (e.g., signs of acceptance) govern subsequent affective, motivational, and behavioral processes that promote friendship development and maintenance (Bhanji & Delgado, 2014; Eisenberger & Cole, 2012; Fareri & Delgado, 2014; Vrticka, 2012). Specifically, increases in positive emotions (Vittengl & Holt, 2000) motivate people to seek out future opportunities to connect with others (Whelan & Zelenski, 2012), thereby creating a self-perpetuating cycle supporting the initiation and strengthening of social bonds (Ramsey & Gentzler, 2015). The current findings build upon earlier research (Kashdan & Roberts, 2004), which together suggest that similar positive affective-relationship formation processes operate for individuals with SAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, state authenticity is associated with fun, with social contact, with being in familiar surroundings, with having one's psychological needs met, with high self-esteem, and with the experience of (Fleeson & Wilt, 2010;Sheldon et al, 1997). Thus, situations that give rise to authenticity are also ones that give rise to positive mood (or that inhibit negative mood) and vice versa (Whelan & Zelenski, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that a positive affective state results in interpersonal attraction (Gouaux, ), sociability, and identification (Ilies, Scott, & Judge, ; Isen, ; Isen & Levin, ). When people are primed with a positive mood, they are more likely to feel sociable and exhibit a stronger preference for social situations, as compared to those under a negative mood (Whelan & Zelenski, ). Therefore, we infer that teams with stronger positive affective tone are more likely to be sociable and hence experience stronger team cohesion and identification.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%